Hyperuricemia is a risk factor for the onset of impaired fasting glucose in men with a high plasma glucose level: a community-based study. - Teruki Miyake; Teru Kumagi; Shinya Furukawa; Masashi Hirooka; Keitarou Kawasaki; Mitsuhito Koizumi; Yasuhiko Todo; Shin Yamamoto; Masanori Abe; Kohichiro Kitai; Bunzo Matsuura; Yoichi Hiasa (PLoS ONE, 2014)
Background It is not clear whether elevated uric acid is a risk factor for the onset of impaired fasting glucose after stratifying by baseline fasting plasma glucose levels. We conducted a community-based retrospective longitudinal cohort study to clarify the relationship between uric acid levels and the onset of impaired fasting glucose, according to baseline fasting plasma glucose levels. Methods We enrolled 6,403 persons (3,194 men and 3,209 women), each of whom was 18-80 years old and had > 2 annual check-ups during 2003-2010. After excluding persons who had fasting plasma glucose levels ≥ 6.11 mM and/or were currently taking anti-diabetic agents, the remaining 5,924 subjects were classified into quartiles according to baseline fasting plasma glucose levels. The onset of impaired fasting glucose was defined as fasting plasma glucose ≥ 6.11 mM during the observation period. Results In the quartile groups, 0.9%, 2.1%, 3.4%, and 20.2% of the men developed impaired fasting glucose, respectively, and 0.1%, 0.3%, 0.5%, and 5.6% of the women developed impaired fasting glucose, respectively (P trend <0.001). After adjusting for age, body mass index, systolic blood pressure, triacylglycerols, high density lipoprotein-cholesterol, creatinine, fatty liver, family history of diabetes, alcohol consumption, and current smoking, uric acid levels were positively associated with onset of impaired fasting glucose in men with highest-quartile fasting plasma glucose levels (adjusted hazard ratio, 1.003; 95% confidence interval, 1.0001-1.005, P = 0.041). Conclusions Among men with high fasting plasma glucose, hyperuricemia may be independently associated with an elevated risk of developing impaired fasting glucose.